Sphaerobolus stellatus: Cannonball Mushroom from West Java - Rudy Hermawan; Indra Maulana (Perhimpunan Mikologi Indonesia, 2020)
Cannonball mushroom is known as the unique genera in Basidiomycetes. This micro-mushroom is the first recorded in Indonesia. The specimen was deposited into Herbarium Bogoriense with code BO 24422. The Sphaerobolus was found on the rotten wood in Landscape Arboretum of IPB University. The fruiting body has similar morphology between Geastrum and Pilobolus. The mushroom has an exoperidium (like Geastrum outer) and endoperidium (like Pilobolus head). The basidiospore is hyaline, globose to elongate, and having circular gradation on the surface. Sphaerobolus is known as lignicolous, phototrophic, and sometimes as coprophilous fungus. Sphaerobolus was classified into Geastrales and Sphaerobolaceae. BO 24422 specimen is classified as S. stellatus.